Vegetation Dispersion in Green Open Space of Universitas Pendidikan Indonesia - Kastolani, Wanjat; Setiawan, Iwan; ., Kusnadi; Paramita, Beta (International Journal of Engineering and Technology, 2018)
A study on the implementation of eco-campus in terms of vegetation suitability in green open spaces at Universitas Pendidikan Indonesia (UPI) had been conducted. The purposes of the study were to analyze the actual condition the vegetation in green open spaces at UPI and to analyze the suitable vegetation to be implemented in green open spaces at UPI to support eco-campus. The study employed a descriptive design using cross section approach which studies a certain object in a certain period of time. To distribute the plants, this study used block unit mapping with the help GPA and a program namely ArcGIS. The results of the study show that most (43.51%) of the existing plants at UPI were herbs; 32.82% of them were trees, 18.32% were shrubs, and 2.29% were bushes. In the meantime, in terms of the plantsâ€™ function, most of the vegetation at UPI were decorative plants (34.35%), followed by medicinal plants (15.27%) and crops (14.5%). In addition to the aforementioned categories, there were 131 species of vegetation around UPI which mostly lied in the east side of the campus particularly around Isola building. Some of them were Filicium decipiens, Pinus merkusii, Barringtonia asiatica, Artocarpus altilis, Terminalia catappa, Agathis dammara, Lagerstoemia flos-reginae, Tabebuia capitata, Cassuarina equisettifolia,Â Mangifera indica, Delonix regi), Bougainvillea spectabillis, Muntingia callabura, and so on. Some were also plants that could only found in certain places such as Elaeocarpus grandiflorus, Mimusops elengi, Altingia exelsa, Elaeocarpus sphaericus, Pterocarpus indicus, Samanea saman, Claoxylon polot, Tectona grandis, Flacourtia inermis, Garcinia mangostana, Ponentia pinnata, Sandoricum koetjape, Brunfelsia uniflora, and Alstonia sholaris. Based on the results of the study, it was also proven that the distribution of the vegetation at UPI was uneven; it focused on certain areas such as gardens and main roads. Â